1988
DOI: 10.1093/icb/28.3.863
|View full text |Cite
|
Sign up to set email alerts
|

Energy Allocation in Mammalian Reproduction

Abstract: SYNOPSIS. On behavioral, hormonal, and physiological grounds, mammalian reproduction can be compartmentalized into the following continuous sequence of events: mating (courtship, estrous), gestation, parturition, lactation, post-lactational parental care, and maternal recovery. We point out that comparing the relative allocation of energy for these events across mammals is difficult because of life history variability (e.g., litter size, birth weight), allometry, phylogeny, and individual variation. We review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
530
2
12

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 739 publications
(553 citation statements)
references
References 96 publications
9
530
2
12
Order By: Relevance
“…This care is energetically costly for females. Lactation is the most energetically expensive component of reproduction for female mammals (see review in Gittleman and Thompson, 1988), and callitrichid females have been observed to lose weight (cotton-top tamarins: Sánchez et al, 1999) and significantly increase their energetic intake (cotton-top tamarins: Kirkwood and Underwood, 1984;saddle-back tamarins: Goldizen, 1987) during lactation. Carrying callitrichid infants comes at a 21% increase in the caloric cost (per minute) of traveling (Tardif, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…This care is energetically costly for females. Lactation is the most energetically expensive component of reproduction for female mammals (see review in Gittleman and Thompson, 1988), and callitrichid females have been observed to lose weight (cotton-top tamarins: Sánchez et al, 1999) and significantly increase their energetic intake (cotton-top tamarins: Kirkwood and Underwood, 1984;saddle-back tamarins: Goldizen, 1987) during lactation. Carrying callitrichid infants comes at a 21% increase in the caloric cost (per minute) of traveling (Tardif, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…data), indicate that T. apereoides reproduce mainly during the dry season. If this is indeed the reproductive pattern, presumably then smaller DHRs in the dry season, as well as other parameters, might be a consequence of female reproductive activities, because more energy would need to be allocated to reproduction (mating, feeding and care of pups) (GITTLEMAN & THOMPSON 1988), at the expense of energy expended in movements. Therefore, it is expected that there is some relationship Table I.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that for species that reproduce in a time of lower food availability, females may show a pattern of smaller displacement. In mammals, the greater parental investment lies with the females (TRIVERS 1972, GITTLEMAN & THOMPSON 1988; therefore, the females tend to conserve energy expended in movement, establishing lower home ranges (LORETTO & VIEIRA 2005). In Panamá, for the spiny rat Proechimys semispinosus (Tomes, 1860), ENDRIES & ADLER (2005) observed that individuals of both the sexes had larger home ranges during the rainy season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this phase of development, females nurse their infants every few hours (common marmoset: Missler et al, 1992) and, along with other group members, carry infants more than 90% of the time (common marmoset; cottontop tamarin; golden lion tamarin, Leontopithecus rosalia; saddle-back tamarin, S. fuscicollis; silvery marmoset, C. argentata; see review in Tardif et al, 1998). This care is energetically costly for females; lactation is the most energetically expensive component of reproduction for female mammals (see review in Gittleman and Thompson, 1988), and infant carrying comes at a 21% increase in the caloric cost of traveling (Tardif, 1996). We operationally defined conception APID as conception occurring 4 weeks following birth, and later.…”
Section: Subjects and Housingmentioning
confidence: 99%